Pharmacokinetics, Safety, and Efficacy of Intravitreal Digoxin in Preclinical Models for Retinoblastoma - Winter, Ursula Andrea (2015)
PURPOSE:To assess in vitro cytotoxic activity and antiangiogenic effect, ocular and systemic disposition, and toxicity of digoxin in rabbits after intravitreal injection as a potential candidate for retinoblastoma treatment.METHODS:A panel of two retinoblastoma and three endothelial cell types were exposed to increasing concentrations of digoxin in a conventional (72-hour exposure) and metronomic (daily exposure) treatment scheme. Cytotoxicity was defined as the digoxin concentration that killed 50% of the cells (IC50) and was assessed with a vital dye in all cell types. Induction of apoptosis and cell-cycle status were evaluated by flow cytometry after both treatment schemes. Ocular and systemic disposition after intravitreal injection as well as toxicity was assessed in rabbits. Electroretinograms (ERGs) were recorded before and after digoxin doses and histopathological examinations were performed after enucleation.RESULTS:Digoxin was cytotoxic to retinoblastoma and endothelial cells under conventional and metronomic treatment. IC50 was comparable between both schedules and induced apoptosis in all cell lines. Calculated vitreous digoxin Cmax was 8.5 μg/mL and the levels remained above the IC50 for at least 24 hours after intravitreal injection. Plasma digoxin concentration was below 0.5 ng/ml. Retinal toxicity was evident after the third intravitreal dose with considerable changes in the ERG and histologic damage to the retina.CONCLUSIONS:Digoxin has antitumor activity for retinoblastoma while exerting antiangiogenic activity in vitro at similar concentrations. Metronomic treatment showed no advantage in terms of dose for cytotoxic effect. Four biweekly injections of digoxin led to local toxicity to the retina but no systemic toxicity in rabbits.